2021
DOI: 10.1038/s41467-020-20469-6
|View full text |Cite
|
Sign up to set email alerts
|

Very low mutation burden is a feature of inflamed recurrent glioblastomas responsive to cancer immunotherapy

Abstract: Several immunotherapy clinical trials in recurrent glioblastoma have reported long-term survival benefits in 10–20% of patients. Here we perform genomic analysis of tumor tissue from recurrent WHO grade IV glioblastoma patients acquired prior to immunotherapy intervention. We report that very low tumor mutation burden is associated with longer survival after recombinant polio virotherapy or after immune checkpoint blockade in recurrent glioblastoma patients. A relationship between tumor mutation burden and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 30 publications
5
58
0
Order By: Relevance
“…We also obtain PD-L1 positivity level and tumor mutational burden (TMB) on all tumors which has implications for immunotherapy (IT) use. Recent data indicates that glioma tumors with low TMB are more likely to respond to IT (19). Clinical trials have demonstrated that IT can work for intracranial metastatic disease (20,21).…”
Section: Methodsmentioning
confidence: 99%
“…We also obtain PD-L1 positivity level and tumor mutational burden (TMB) on all tumors which has implications for immunotherapy (IT) use. Recent data indicates that glioma tumors with low TMB are more likely to respond to IT (19). Clinical trials have demonstrated that IT can work for intracranial metastatic disease (20,21).…”
Section: Methodsmentioning
confidence: 99%
“…Survival differences were maintained after excluding IDH-mutated, MGMT methylated, and hypermutated patients and were not related to steroid dosage [68]. Notably, these associations were not showed in primary GBM patients [68]. Accordingly, in a recent observational study, 13 patients (eight GBM, four anaplastic astrocytomas, one anaplastic oligodendroglioma) with partial or complete loss of mismatch repair proteins had no apparent clinical benefit from pembrolizumab treatment (median PFS 2.2 months, median OS 5.6 months, no partial or complete response) [69].…”
Section: Biomarkersmentioning
confidence: 87%
“…Transcriptomic analyses also showed enriched inflammatory gene signatures in recurrent GBM tumors with a low TMB [68]. Survival differences were maintained after excluding IDH-mutated, MGMT methylated, and hypermutated patients and were not related to steroid dosage [68]. Notably, these associations were not showed in primary GBM patients [68].…”
Section: Biomarkersmentioning
confidence: 93%
See 2 more Smart Citations